A novel structured nanosized CaO on nanosilica surface as an alternative solid reducing agent for hydrogen fluoride removal from industrial waste water. (1st February 2019) - Sadhasivam, T.; Lim, Min-Hwa; Jung, Do-Sung; Lim, Hankwon; Ryi, Shin-Kun; Jung, Ho-Young
Abstract: In the semiconductor industry, perfluorinated compound removal is a major concern owing to the formation of highly toxic and hazardous hydrogen fluoride (HF) as a by-product. Calcium oxide (CaO) can be considered a promising material for HF sorption reaction process. However, the easier reaction between CaO and H2 O results in the formation of Ca(OH)2, which ultimately limits the usefulness of CaO. The objective of the research work is preparation of CaO nanoparticles on hydrophobic silica (SiO2 ) to use as a alternative solid reducing catalyst for efficient HF removal process. High-resolution transmission electron microscopy micrographs confirmed that the as-prepared CaO particles are <5 nm in size and the smaller sized CaO nanoparticles are homogeneously anchored on the entire surface of ∼100 nm spherical SiO2 nanoparticles. The reaction-enhanced regenerative catalytic system (RE-RCS) was used to measure the HF removal efficiency. HF is removed more efficiently using CaO on SiO2 than using CaO alone. At the outlet of the RE-RCS, the obtained HF concentrations are 2811.4 and 2166.1 ppm after a 3 h reaction using CaO and CaO on SiO2 as the sorbent, respectively. The lower concentration of HF at the outlet of the system using CaO on SiO2 indicates that HF sorption is remarkably enhanced using CaO on SiO2 inside the RE-RCS. In addition, the presence of a hydrophobic region in the catalyst sorbent prevents the reaction between CaO and water, which leads to avoiding the formation of Ca(OH)2 . These phenomena significantly enhance the HF removal efficiency and CaF2 formation process. Graphical abstract: The as-prepared new sorbent material consisting of CaO nanoparticles on hydrophobic SiO2 nanoparticles can be considered an efficient solid reducing agent for highly hazardous HF removal. In addition, the by-product CaF2 can be considered for use in ceramics, building materials, and biomedical components. Image 1 Highlights: CaO (<5 nm in size) homogeneously anchored on the entire surface of ∼100 nm SiO2 . CaO on hydrophobic SiO2 used as a solid reducing catalyst for HF removal process. Hydrophobic region in the catalyst sorbent prevents the formation of Ca(OH)2 . The HF removal efficiency is increased by the addition of SiO2 to the CaO sorbent.